Qumran Hebrew : an overview of orthography, phonology, and morphology - Reymond, Eric D. (Resources for biblical study (Brill Academic Publishers), 2014)
This book explores salient topics in Hebrew orthography, phonology, and morphology from the Dead Sea Scrolls. The book, helpfully divided into short sections that treat specific linguistic phenomena, presents a synopsis of previous research and critiques this research by, among other things, considering evidence from recently published scrolls. Reymond argues that several grammatical matters distinguish his study from previous studies of Hebrew in the Dead Sea Scrolls. First, he emphasizes problems posed by scribal errors and highlights some of the more obvious examples of these. He also argues that gutteral letters had not all "weakened" to the point of not being pronounced and/or being confused with each other, as some have implied. Rather, the guttural letters each show a distinct distribution, suggesting that they were "weak" in specific linguistic environments and in specific texts and/or dialects. Lastly, Reymond shows that certain phonetic shifts (such as the shift of yodh> aleph and the opposite shift of aleph> yodh) occur in discernible linguistic contexts that suggest this was a real phonetic phenomenon.